Vegetación y flora acuáticas de la laguna de Yuriria, Guanajuato, México - Ramos Ventura, Leandro J.; Novelo Retana, Alejandro (Instituto de Ecología, A.C., 1993)
The research work was carried out at Yuriria lagoon, in the state of Guanajuato, in order to know its vascular aquatic flora and vegetation, and to recognize the plant associations. Although the Yuriria lagoon is artificial (a dam), it presents a floristic richness which includes 47 species in 34 genera and 25 families of vascular plants. Gramineae, Cyperaceae, Compositae, Lemnaceae, Polygonaceae and Umbelliferae are the best represented families. The dominant life form is herbaceous and the attached emergent hydrophytes reach a total of 27 species. Only 2 arboreal elements (Taxodium mucronatum and Salix chilensis) were recorded. The principal aquatic vegetation of the lagoon, especially in shallow places at the south and southeast, is represented by extensive stands of cat tail (Typha domingensis) and bulrush (Scirpus californicus). The lagoon is in a clear aging process with the result of a continuous loss of aquatic habitats, which can be partially explained as due to spread of Eichhornia crassipes (waterhyacinth) which covers 60% of the surface. This situation is becoming more critical and in a short time the lagoon may disappear if the right measures to reestablish the equilibrium in the Lerma-Santiago basin, which is the main source of this aquatic environment, are not taken.